Evaluasi Kompetensi terhadap Peningkatan Komitmen dan Kinerja ASN - Jefirstson Richset Riwukore (Jurnal Nusantara Mengabdi, 2023)
Purpose: Provide knowledge and skills to employees to be able to analyze and evaluate increased commitment and performance based on employee competency management at the Kupang City Government Secretariat.. Methodology: This PkM implementation method uses lecture and training techniques, which are generally known as focus group discussions (FGD) and workshops. Activity partners are determined by purposive sampling technique (deliberately) based on the organizational structure of the Kupang City Government which is at the Echelon II level (Department/Agency), which consists of 28 SKPD (Badan/Department). Based on this, the participants are determined by quota sampling technique, namely, the PkM activity participants are the direct leaders of the organization with the rank/position/class of Echelon II, the Heads of Service, and Heads of the Agency. Thus the participants who took part in this PkM activity were 28 participants. Results: The results of PkM activities were evaluated using a SWOT analysis tool, where participants were asked to formulate organizational conditions based on the internal environment (strengths and weaknesses) and the external environment (opportunities and threats) based on the knowledge management presented by the resource persons. Then, a solution strategy concept was developed based on the SWOT matrix. Contribution: This training can increase the knowledge and skills of employees in analyzing and evaluating employee commitment and performance from the aspect of motivation using the SWOT analysis method.